Income inequality convergence across EU regions - Savoia, Francesco (Luxembourg, 2019)
"Economic inequality has increased in many EU countries in the last decades. Yet, efforts assessing economic disparities across the EU regions mostly concentrate on convergence in average per capita incomes, offering much less evidence on how regional income is distributed. Using data from Luxembourg Income Study (LIS) over the 1989-2013 period, this study contributes to fill this gap, focusing on whether there has been convergence of income distribution among EU regions, and on to what extent regional initial conditions and the Cohesion Policy affect the convergence process. Crosssection and panel convergence regressions, after a number of robustness checks, indicate that NUTS 2 regions are converging to higher level of income inequality, so becoming equally more unequal. This process is significantly faster when regions share similar structural characteristics. Finally, the implementation of the Cohesion Policy seems to have significantly accelerated the pace of convergence."